Penetrating neck injuries: a guide to evaluation and management - Nowicki, JL (Ann R Coll Surg Engl, 2018)
INTRODUCTION: Penetrating neck injury is a relatively uncommon trauma presentation with the potential for significant morbidity and possible mortality. There are no international consensus guidelines on penetrating neck injury management and published reviews tend to focus on traditional zonal approaches. Recent improvements in imaging modalities have altered the way in which penetrating neck injuries are now best approached with a more conservative stance. A literature review was completed to provide clinicians with a current practice guideline for evaluation and management of penetrating neck injuries. METHODS: A comprehensive MEDLINE (PubMed) literature search was conducted using the search terms ‘penetrating neck injury’, ‘penetrating neck trauma’, ‘management’, ‘guidelines’ and approach. All articles in English were considered. Articles with only limited relevance to the review were subsequently discarded. All other articles which had clear relevance concerning the epidemiology, clinical features and surgical management of penetrating neck injuries were included. RESULTS: After initial resuscitation with Advanced Trauma Life Support principles, penetrating neck injury management depends on whether the patient is stable or unstable on clinical evaluation. Patients whose condition is unstable should undergo immediate operative exploration. Patients whose condition is stable who lack hard signs should undergo multidetector helical computed tomography with angiography for evaluation of the injury, regardless of the zone of injury. CONCLUSIONS: The ‘no zonal approach’ to penetrating neck trauma is a selective approach with superior patient outcomes in comparison with traditional management principles. We present an evidence-based, algorithmic and practical guide for clinicians to use when assessing and managing penetrating neck injury.